Influence of Hot Water and 1-Methylcyclopropane Treatments on Air-Stored Quince Fruit - Nurdan Tuna Gunes; Ender Sinan Poyrazoğlu (Agronomy, 2022)
The commercial application potential of hot water treatments against 1-Methylcyclopropane (1-MCP) treatments for maintaining quality of fruit in quince (Cydonia oblonga Mill. cv. ‘Eşme’) during long-term regular air storage was investigated. The fruits were treated with either hot water at 50 ± 1 °C for 3 and 5 min or two different 1-MCP (SmartFreshSM) concentrations (300 ppb and 1000 ppb) at 12 °C for 20 h. Then, all fruits were stored at 0 ± 1 °C temperature, 85–90% relative humidity and regular air conditioning for 6 months. The efficacy of postharvest treatments in some fruit treats was monitored at monthly intervals. Postharvest treatments did not remarkably affect physiological features of fruits, such as ethylene production and respiration rate. Hot water treatments and 1000 ppb 1-MCP treatments positively maintained flesh color, acidity, malic acid content, 5–caffeoylquinic acid and vitamin C levels, and alleviated flesh firmness and sensory expert analysis scores. Overall, hot water treatment, a non-chemical treatment, had a potential for maintaining quality in quince fruit during long-term regular air storage at 0 ± 1 °C temperature and 85–90% relative humidity conditions for 6 months.